PERBANDINGAN MODEL MATEMATIKA KURVA PRODUKSI AYAM PETELUR DI CV CANDI FARM KECAMATAN TALANG KELAPA KABUPATEN BANYUASIN : MATHEMATICS MODEL COMPARISON LAYER PRODUCTION CURVE IN CV CANDI FARM, TALANG KELAPA DISTRICT, BANYUASIN REGENCY KURVA PRODUKSI AYAM PETELUR DI CV CANDI FARM KECAMATAN TALANG KELAPA KABUPATEN BANYUASIN (Jurnal Peternakan Nusantara, 2022)
Chicken eggs are in great demand by the public, because apart from being easy to obtain, the price is quite affordable, has a high nutritional content, tastes good and can be processed into various kinds of food products. The growth of poultry will form a curve with a certain mathematical model. Objectives of the study 1) To determine the shape of the egg production curve at CV Candi Farm aged 20-90 weeks. 2) Obtain the most appropriate equation for estimating the egg production curve at CV Candi Farm aged 20-90 weeks. 3) Obtain actual and estimated standards of chicken egg production at CV Candi Farm aged 20-90 weeks. The data used for this study were taken from CV Candi Farm. The models tested in this study are the Wood model, the Mc Nally model, the Mc Millan model, the compartment model, the Yang model, the Adams-Bell model, and the logistics model. The results showed that the egg production curve was sigmoid in shape. Egg production increases rapidly in the first weeks of production until it reaches a peak at week 43. After reaching the peak, egg production continued to decline at a decreasing rate of about 1-5% per week, the most appropriate equation for estimating chicken egg production at CV Candi Farm aged 20-90 weeks was the Adams-Bell model with R2 = 0.9892, r = 0.989, and SE = 1.269 and the actual production standard and the estimated egg production of CV Candi Farm chicken eggs aged 20-90 weeks is the Adams-Bell model.